Sustainable and open sorption system for low‐temperature heat storage applications. (9th April 2022) - Padamurthy, Ankammarao; Nandanavanam, Jalaiah; Rajagopalan, Parameshwaran
Summary: In the present study, an open sorption thermochemical energy storage (TCES) system was developed and investigated experimentally for low‐temperature heat storage applications using zeolites. Desorption and adsorption experiments were carried out sequentially for 15 cycles to study the energy storage and retrieval characteristics. Further, the performance characteristics were analysed to find the system's suitability for intended applications. The charging and discharging processes were carried out respectively at around 95°C and room temperature, for zeolite 13X and zeolite 4A. Zeolite 13X exhibited better average total energy storage density during the desorption and adsorption and they are respectively 129.4 and 57 kWh/m 3 . The average cumulative energy storage efficiency for zeolite 13X and zeolite 4A are respectively 44.1% and 24%. Similarly, the average exergy efficiency for zeolite 13X and zeolite 4A are respectively 21.5% and 11%. For the tested thermochemical materials (TCMs), the deviations in mass change due to multi‐cycle test‐run was small and hence suitable for long‐term usage without concern about their stability. The present study has demonstrated the technical competence in utilizing the energy sources (eg, solar energy, industrial waste heat) towards low‐temperature heat storage applications, viz. building's space heating and water heating.